The world in Auerbach's mouth: Weltliteratur after philhellenism. (28th August 2019) - Umachandran, Mathura
Abstract: We live in an age of globalized and globalizing phenomena: the contemporary agenda of academic inquiry takes in 'networks', 'connectivity', and other modes of articulating complex structures of human activity. In Comparative Literature and beyond, the idea of world literature has borne the weight of idealist intercultural understanding, the hopes of translation studies, and the anxieties around the failure of communication. Erich Auerbach offers a touchstone in the conceptual genealogy of world literature ( Weltliteratur ). This article illuminates how Auerbach's Weltliteratur is predicated on a polemic with German philhellenism, tracked through Auerbach's declaration that his idea is 'ungoethisch' . Auerbach's revisions to Weltliteratur constituted a strategy to render it a historicist concept. Since Auerbach's notion of historicism was itself derived from nineteenth-century German humanism, this essay argues that Auerbach was attempting to go with Goethe beyond Goethe. Finally, this essay assesses how successful Auerbach's decoupling of Weltliteratur from universalism, under the sign of Goethe and the Greeks. I suggest that Weltliteratur is still a pertinent concept today because of Auerbach's intervention to install historicist and dialectical resources therein.